Analysis of the role of copper impregnated composite hard surfaces, bed linens and patient gowns in reducing healthcare-associated infection rates - Burke, Gene H; Butler, Jacqueline P (International Journal of Infection Control, 2018)
The aim of this study was to evaluate the impact of copper-impregnated composite hard surfaces, bed linens and patient gowns on healthcare-associated infections (HAIs). We took in account potentially confounding factors of new construction and Det Norse Veritas Managing Infection Risk (DNV MIR) certification to mitigate risk of HAIs, multi drug resistant organisms (MDRO) and Clostridium difficile HAIs. The study was conducted in the acute care units from three hospitals within a regional healthcare system and these were assessed retrospectively. Facility 1 and Facility 2 shared the circumstance of new construction. Facility 1 and Facility 3 shared the processes of DNV-MIR. Only Facility 1 undertook the intervention of copper-impregnated hard surfaces, bed linens and patient gowns. We compared infection rates (IR) following their normalization per 10,000 patient hospitalization days before and after complete implementation of copper-impregnated composite hard surfaces, bed linens and patient gowns. Facility 1 had a 28% reduction in total C. difficile and MDRO IR, while Facilities 2 and 3 had 103% and 48% increases in total IR respectively. Although the rate changes per facility were not statistically significantly changed from baseline (p>0.05), there was consistent divergence between the IR at the copper enabled facility and the others. As this divergence occurred when other pertinent factors were constant between them, including new construction and new processes for mitigation of infection risks, these outcomes support the contention that copper-impregnated linens and composite hard surfaces were shown to reduce HAI rates.